Mobility and participatory planning in bogotá and medellín: relationship with cities in colombia and south america (2012)
The article approaches the issue of urban mobility in Colombia by means of analyzing different bodies of data such as: population growth in five national cities, Bogota's institutional development over the last twenty years, successful participatory planning in the city of Medellín, effects of economic conurbation in large urban centers, the successful implementation of public transportation systems in comparison with other South American metropolis, Bogota's road and street condition, and the increasing rate of vehicle ownership in four capital cities. The author concludes, among others, that the best solution to the ever-growing problem of mobility in Colombian cities is the uninterrupted and well-managed execution of public transportation systems in a creative and prospective manner.